Fortunella japonica extract as a reducing agent for green synthesis of silver nanoparticles - Phung Anh, Nguyen; Thi Ai Mi, Truong; Huynh Thanh Linh, Duong; Thi Thuy Van, Nguyen; Tien Cuong, Hoang; Van Minh, Nguyen; Tri, Nguyen (International Journal of Engineering and Technology, 2018)
A rapid way of synthesizing silver nanoparticles (AgNPs) by treating Ag+ ions with a green Fortunella Japonica (F.J.) extract as a combined reducing and stabilizing agent was investigated. The reaction solutions were monitored using UV-Vis spectroscopy, the size and shape of crystals were determined by scanning electron microscopy and transmission electron microscopy, the crystalline phases of AgNPs were presented by Xâ€“ray diffraction, and the relation of nanoparticles with Fortunella Japonica extract was confirmed using fourier transform infrared spectroscopy. The results indicated that no formation of AgNPs had taken place in the dark during 24 hours at room temperature and 40 oC. Meanwhile, it was found that the rate of AgNPs formation increased rapidly under the sunlight. The effects of the synthesis factors on the AgNPs formation were investigated. The suitable conditions for the synthesis of AgNPs using F.J. extract were determined as follows: F.J. extract was mixed with AgNO3 1.75 mM solution with the volume ratio of 3.5 AgNO3 solution/1.5 F.J. Extract, stirred 300 rpm for 150 minutes at 40 oC under sunlight illumination. At these conditions, AgNPs showed high crystalline structure with the average size of 15.9 nm. The antibacterial activity of silver nanoparticles was determined by agar well diffusion method against E. coli and B. subtilis bacteria. The green synthesized AgNPs performed high antibacterial activity against both bacteria.Â Â